Opinions of Fine Arts Students about Their Profession and Their Expectations from the Future - Mustafa Yeniasır; Burak Gökbulut (MDPI AG, 2018)
Art emerged the moment humankind existed. Today it is seen that art exists everywhere humans do. It is essential for the future of nations that art and culture is maintained and transferred to next generations. For this reason, developed or developing nations give considerable value to the education of art and conduct studies so as to increase its quality constantly. Fine Arts High Schools which are established for this purpose aim at educating individuals who have self-confidence in society, who think and criticize. In addition, they aim at creating artistic and cultural awareness in students through Fine Arts High Schools and make contribution to the free thinking of individuals in an environment where art is produced. In this study, the opinions of 100 students chosen with convenience sampling who are enrolled at two different art schools (Nicosia Anatolian Fine Arts High School and Atatürk Vocational High School) in Northern Cyprus are consulted as regards the branch of art they are studying and an effort is paid to display where they see themselves in this field in the future. Besides, based on student opinions, an effort is paid to determine the viewpoint of Cypriot Turks towards art and recommendations are made for the development of fine arts education in Northern Cyprus with the obtained results. An evaluation of the results of the research shows that a majority of both female and male students are planning to continue with the branch of art they are studying and that they are satisfied with the education they receive. In addition, it is concluded that the expectations of the majority of students at their entrance to the art school are met and that the students have a negative perception as regards the viewpoint of Cypriot Turkish community towards art.